On Generalized Rational α−Geraghty Contraction Mappings in G−Metric Spaces - N. Priyobarta; Bulbul Khomdram; Yumnam Rohen; Naeem Saleem (Journal of Mathematics)
In this paper, we discuss about various generalizations of α−admissible mappings. Furthermore, we extend the concept of α−admissible to generalize rational α−Geraghty contraction in G−metric space. With this new contraction mapping, we establish some fixed-point theorems in G−metric space. The obtained result is verified with an example.